ANALISA SIFAT MEKANIK MATERIAL KOMPOSIT BERPENGUAT SERAT AMPAS TEBU BERMATRIKS EPOXY BERDASARKAN VARIASI KONSENTRASI NaOH PADA PROSES ALKALISASI SERAT - Rydho Putra Pradana (JEECAE (Journal of Electrical, Electronics, Control, and Automotive Engineering), 2024)
Material innovations that are more environmentally friendly continue to be created in this era. Natural fiber composite materials continue to be researched and developed as alternative materials to synthetic fiber plastics, due to their strong, lightweight and environmentally friendly properties compared to synthetic fiber plastics. In this study, the composite material consists of epoxy resin as the matrix and bagasse fiber as the reinforcement. This study was conducted to determine the mechanical properties of epoxy matrix bagasse fiber reinforced composites with unidirectional fiber orientation using the hand lay-up method based on variations in 7%, 11% and 15% NaOH concentrations in the fiber alkalization process. Analysis of mechanical properties carried out is reviewed from ASTM D790 standard bending testing and ASTM D638-01 standard tensile testing. The results of bending test data obtained, namely the highest bending strength is located at 15% NaOH concentration with an average value of 98,58 N/mm2 and the lowest bending strength is located at 7% NaOH concentration with an average value of 88,99 N/mm2. As for the results of tensile testing data obtained, the highest tensile stress is located at 15% NaOH concentration with an average value of 51,36 N/mm2 and the lowest tensile stress is located at 7% NaOH concentration with an average value of 41,33 N/mm2. From the results of bending and tensile testing, it is concluded that the higher the NaOH concentration in the fiber alkalization process, the more the mechanical strength value of each specimen increases.